Operations research applications and algorithms - Winston, Wayne L.; Goldberg, Jeffrey B. (Thomson/Brooks/Cole, 2004)
The market-leading textbook for the course, Winston's OPERATIONS RESEARCH owes much of its success to its practical orientation and consistent emphasis on model formulation and model building. The Student Suite CD-ROM, which now accompanies every new copy of the text, contains the latest versions of commercial software for optimization, simulation, and decision analysis.